OCCURRENCE AND GENESIS OF THUNDER EGGS CONTAINING PLUME AND MOSS AGATE - Kile D.E. (My University, 2002)
Examines the occurrence and genesis of thunder eggs containing plume and moss agate. Description of the surface textures of staples; Components of thunder eggs; Documentation of the occurrence of nodules on rhyolite.
Keywords: AGATES